Performance based navigation - Луппо, О.Є.; Лазоренко, В.А.; Губаренко, А.С. (Proceedings of National Aviation University, 2010)
Problems and prospect of airspace and air traffic development have been exemined. PBN concept has been defined as effective way to solve problems of airspace and air traffic.